Enantiomers separation by simulated moving bed chromatography. Non-instantaneous equilibrium at the solid-fluid interface - Azevedo, Diana C.S. (1999)
The simulated moving bed (SMB) technology, first conceived for large bulk-scale separations in the petrochemical industry, has found increasingly new applications in the pharmaceutical industry. Among these, the separation of fine chemicals has been the subject of considerable study and research. This work presents the modeling, simulation and design of the operation of a SMB plant in order to separate a binary chiral mixture. The usual assumption of instantaneous equilibrium at the solid–fluid interface is questioned and a first-order kinetics of adsorption is taken into account. The cases of linear, Langmuir and modified Langmuir equilibria are studied. The equivalent true moving bed (TMB) model was used assuming axial dispersion for the fluid flow and plug flow for the solid-phase flow. Intraparticle diffusion was described by a linear driving force (LDF) approximation. Simulation results indicate that, under certain conditions, equilibrium is not actually reached at the adsorbent surface. This leads to different unit performances, in terms of product purities and recoveries, as compared to those predicted assuming instantaneous equilibrium. Moreover, SMB units may be improperly designed by the usual methods (flow-rate ratio separation regions) if non-equilibrium effects are overlooked.